Survey of International Experience in Advanced Metering Infrastructure and its Implementation - World Bank (World Bank, Washington, DC, 2019)
This report packages international know-how around major steps and key questions to be faced by South Asian utilities in the design and deployment of advanced metering infrastructure (AMI). The type of data analytics generated by AMI can lead to a transformation of utilities, and a new generation of demand-side and supply-side efficiency measures, policies, and regulations. In addition, greater communication capabilities between the power sector and its consumers can create stronger customer provider relationships, greater understanding of needs and capabilities, and open pathways to innovation. This report covers international best practices for the end-to-end deployment of an AMI system including such areas as main functions, procurement options, cost recovery models, and the organizational or functional changes needed to implement AMI-enabled business processes. For this report, the study team surveyed a variety of international utilities, including several early adopters of AMI, which collectively represent a notable portion of smart meters deployed globally today, and these are documented in Section 4 under case studies.